2014
DOI: 10.1111/and.12378
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of microsurgical testicular sperm extraction in familial idiopathic nonobstructive azoospermia

Abstract: The aim of the study was to evaluate the sperm retrieval rate by microsurgical testicular sperm extraction (TESE) in familial idiopathic nonobstructive azoospermia (NOA). One hundred and nineteen patients with idiopathic NOA who underwent microsurgical TESE over the past 5 years were included. Patients were then divided into two groups; Group 'A' with familial idiopathic NOA (11 families with two brothers in each family, 22 patients) and Group 'B' with nonfamilial idiopathic NOA (97 patients). Clinical data as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…[2][3][4] Together, these analyses explain the cause of only ~30% of cases of NOA. [5][6][7] It is generally assumed that many of the remaining idiopathic cases have genetic causes, but although variants in ~55 genes have been associated with NOA in humans 8,9 and variants in hundreds of genes are known to impair spermatogenesis in mouse models, [10][11][12] there has been limited prospective, point-of-care, next-generation sequencing assessment of males with idiopathic NOA to determine the fraction with genetic causes. 13 The challenge in identifying genetic variants in idiopathic males is that the high prevalence of NOA, despite the detrimental effect on reproductive fitness, suggests that high genetic heterogeneity underlies this condition.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] Together, these analyses explain the cause of only ~30% of cases of NOA. [5][6][7] It is generally assumed that many of the remaining idiopathic cases have genetic causes, but although variants in ~55 genes have been associated with NOA in humans 8,9 and variants in hundreds of genes are known to impair spermatogenesis in mouse models, [10][11][12] there has been limited prospective, point-of-care, next-generation sequencing assessment of males with idiopathic NOA to determine the fraction with genetic causes. 13 The challenge in identifying genetic variants in idiopathic males is that the high prevalence of NOA, despite the detrimental effect on reproductive fitness, suggests that high genetic heterogeneity underlies this condition.…”
Section: Introductionmentioning
confidence: 99%
“…We found that parameters to forecast testicular SRR have become the particular focus of research over recent years. Researchers have considered several parameters which could act as predictors, including age, testicular volume, histopathology (hypospermatogenesis and Johnsen score), serum FSH, INH-B, TT levels, Y chromosomal microdeletions and family history [ 8 , 14 , 24 , 25 ]. However, other researchers have some that parameters could not be treated as predicators, including age, testicular volume, histopathology (hypospermatogenesis), previous negative TESE, serum FSH, LH, INH-B levels, seminal plasma INH-B, and anti-Müllerian hormone [ 7 , 16 , 21 , 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The two patients in Group A with successful sperm retrieval belonged to one family. The histopathological diagnosis was the same in the brothers for each family [ 25 ]. The associated use of multiple parameters thus increased predicted value.…”
Section: Discussionmentioning
confidence: 99%
“…According to testicular spermatogenic function, azoospermia can be classified as obstructive‐azoospermia (OA) and non‐obstructive‐azoospermia (NOA) (Wosnitzer et al ., ). Although some NOA patients have been identified with sperm in the testis (Arafa et al ., ; Ragab et al ., ), there are negligible possibilities for microsurgical extraction for the part of NOA cases, including those patients with deletion of azoospermia factor a or b (AZFa or AZFb) (Krausz et al ., ). Therefore, screening the AZF regions of the Y chromosome is of great importance to predict the prognosis of management in patients with azoospermia (Krausz & Casamonti, ).…”
Section: Introductionmentioning
confidence: 99%